Morphology effect on photocatalytic activity in Bi3Fe0.5Nb1.5O9. (3rd May 2018) - Yin, Xiaofeng; Li, Xiaoning; Gu, Wen; Zou, Wei; Liu, Huan; Zhu, Liuyang; Fu, Zhengping; Lu, Yalin
Abstract: In this work, the Aurivillius-phase ferroelectric Bi3 Fe0.5 Nb1.5 O9 were synthesized by hydrothermal (BFNO-H) and solid state methods (BFNO-S), respectively. The BFNO-H shows a hierarchical morphology, which is stacked by intersecting single-crystal nanosheets with {001} and {110} exposed facets, while the BFNO-S shows disorganized micron-scale morphology. BFNO-H shows a much stronger photodegradation activity (10.4 times and 9.8 times) than BFNO-S in the visible-light photodegradation of rhodamine B (RhB) and salicylic acid. The higher photodegradation activity of BFNO-H was firstly ascribed to the hierarchical structure and the larger specific surface area (16.586 m 2 g −1 ) because a large specific surface area can increase reactive sites and shorten photogenerated carrier migration distance. However, after being normalized by the specific surface area, BFNO-H still performs better than BFNO-S, implying that the specific surface area is not the only factor that determines the photocatalytic activity. Considering that the built-in electric field originating from spontaneous polarization in Bi3 Fe0.5 Nb1.5 O9 has existed in both ab plane and c direction, it matches well with the {001} and {110} exposed facets of BFNO-H nanosheets. This appropriate matching in BFNO-H nanosheets may improve the separation and transmission of photogenerated electron–hole pairs and further enhance its photocatalytic activity. Moreover, the trapping experiments reveals that holes ( h + ) are the main active species and hole-derived oxidation is the main redox reaction during photodegradation of organic pollutions.